INSECURITY IN IMO STATE NIGERIA: A DIAGNOSIS OF THE CAUSES, ENABLERS AND PATHWAYS TO SUSTAINABLE PEACE IN THE STATE - Amadi C. J; Ohaeri C. S; Maduka P. C (Journal of Social Science, 2026)
Objective: This study diagnoses the security situation in Imo State, identifying the causes and enabling factors that sustains insecurity in parts of the state since 2020. The study was motivated by the need to complement government efforts in peace building and security, which is currently yielding positive results in the areas of dislodging criminal elements from previously occupied communities and hideouts, resettlement of residents who had abandoned their communities and rebuilding infrastructure in various communities destroyed by insecurity, armed banditry and criminality. Method: The methodology of the study was qualitative, using thematic analysis of relevant aspects of the research study. The study was anchored on the Human Security Theory by Mahbub ul Haq. Results: The study identified the causes of insecurity from four schools of thought, namely political, secessionist, opportunistic and sociological schools of thought. Six key enablers were identified, which are community connivance, fear factor, failure of statutory state security agents, existence of ungoverned spaces, ideological enablers and the criminal economy of insecurity. Novelty: The study therefore, recommended, among others, a multi stakeholders’ approach that will involve the Government, the People and the use of Technology (GPT approach).